2017
DOI: 10.33588/rn.6511.2017298
|View full text |Cite
|
Sign up to set email alerts
|

Efecto de la cocaína sobre la inhibición por prepulso de la respuesta de sobresalto

Abstract: Introducción. La inhibición por prepulso (IPP) de la respuesta de sobresalto es una medida de sincronización sensitivomotora basada en la respuesta del reflejo de sobresalto. Un déficit en la IPP se ha observado en pacientes psiquiátricos, especialmente con esquizofrenia, así como en sujetos vulnerables a desarrollarla. Asimismo, los consumidores de cocaína presentan un alto índice de patologías psiquiátricas como la esquizofrenia. Objetivo. Conocer las alteraciones que el consumo de cocaína puede producir en … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 66 publications
0
7
0
1
Order By: Relevance
“…Amphetamine decreases PPI in a strain of rats with a relatively low COMT gene expression in the NAc, while it increases PPI in another strain of rats with relatively high COMT gene expression in the NAc (Talledo et al, 2009). In light of this evidence, DA availability in the NAc seems to be critical in determining the level of PPI observed; i.e., a higher DA level will induce a PPI deficit, while a lower DA level will increase PPI (Arenas et al, 2017). The role of DA in determining PPI levels has been bolstered since activation of midbrain cholinergic neurons has been shown not to mediate PPI levels (Azzopardi et al, 2018).…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Amphetamine decreases PPI in a strain of rats with a relatively low COMT gene expression in the NAc, while it increases PPI in another strain of rats with relatively high COMT gene expression in the NAc (Talledo et al, 2009). In light of this evidence, DA availability in the NAc seems to be critical in determining the level of PPI observed; i.e., a higher DA level will induce a PPI deficit, while a lower DA level will increase PPI (Arenas et al, 2017). The role of DA in determining PPI levels has been bolstered since activation of midbrain cholinergic neurons has been shown not to mediate PPI levels (Azzopardi et al, 2018).…”
Section: Discussionmentioning
confidence: 96%
“…The role of DA in determining PPI levels has been bolstered since activation of midbrain cholinergic neurons has been shown not to mediate PPI levels (Azzopardi et al, 2018). One of the main brain nuclei that modulate PPI is the pedunculopontine tegmentum (PPTg; Arenas et al, 2017), which is one of the major cholinergic centers of the brain (Gut and Winn, 2016). However, it has recently been demonstrated that cholinergic PPTg neurons do not mediate PPI, in contrast to a longstanding hypothesis maintaining that they do (Azzopardi et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…PPI is a good neurobiological marker between different species because it is hereditary and does not become habituated or eliminated over repeated tests [ 9 , 17 , 18 , 19 , 20 ]. Moreover, PPI is reduced in patients with schizophrenia, making it a good endophenotype for this pathology [ 21 , 22 , 23 , 24 , 25 , 26 ], and lower PPI is also associated with antisocial characteristics [ 27 , 28 ]; a recent study used PPI to discriminate between patients with APD alone or APD with psychopathy [ 29 ]. We also previously showed that patients with CRD + SCZ or CRD + APD presented PPI deficits compared to patients with CRD without a DP [ 30 ].…”
Section: Introductionmentioning
confidence: 99%
“…In mice, baseline PPI also correlated with sensitivity to the reinforcing effects of cocaine in the conditioned place preference paradigm; animals with low PPI had higher striatal DA D2 receptor expression and required higher doses of cocaine (12 mg/kg) to acquire a conditioned preference than those with higher PPI [ 9 ]. Thus, DA availability in the NAc appears to be critical in determining the PPI; higher DA levels induce a PPI deficit, while lower DA levels increase PPI [ 21 , 35 ]. Together, these data suggest that patients with lower PPI levels present dopaminergic system alterations that increase their vulnerability to CRD.…”
Section: Introductionmentioning
confidence: 99%